2023
DOI: 10.3389/fpubh.2023.1031457
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis for the overall health status of elderly, multimorbid patients with diabetes

Abstract: PurposeTo evaluate the overall health status and health-related abilities and problems of elderly patients with diabetes and multimorbidity compared with those with diabetes only. Additionally, we aimed to identify different subgroups of elderly, multimorbid patients with diabetes.MethodsThis cross-sectional study included 538 elderly patients with diabetes. The participants completed a series of questionnaires on self-rated health (SRH), diabetes self-management, self-efficacy, health literacy, depression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Using a similar definition of multimorbidity, a previous study in the United States found the prevalence of multimorbidity in diabetes patients to be 92% ( Kerr et al, 2007 ), which is similar to the present findings. We also found the prevalence of multimorbidity in diabetes patients to be slightly higher in women than in men, which is consistent with a previous finding ( Bing et al, 2023 ). A potential explanation for the higher prevalence in women is the structural placement of women in society ( Arber and Cooper, 1999 ).…”
Section: Discussionsupporting
confidence: 93%
“…Using a similar definition of multimorbidity, a previous study in the United States found the prevalence of multimorbidity in diabetes patients to be 92% ( Kerr et al, 2007 ), which is similar to the present findings. We also found the prevalence of multimorbidity in diabetes patients to be slightly higher in women than in men, which is consistent with a previous finding ( Bing et al, 2023 ). A potential explanation for the higher prevalence in women is the structural placement of women in society ( Arber and Cooper, 1999 ).…”
Section: Discussionsupporting
confidence: 93%